2022
DOI: 10.1007/s00535-022-01879-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer and genomics: review of literature

Abstract: Gastric cancer (GC) is a major health concern in many countries. GC is a heterogeneous disease stratified by histopathological differences. However, these variations are not used to determine GC management. Next-generation sequencing (NGS) technologies have become widely used, and cancer genomic analysis has recently revealed the relationships between various malignant tumors and genomic information. In 2014, studies using whole-exome sequencing (WES) and whole-genome sequencing (WGS) for GC revealed the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 66 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…However, while the role of T cells has made some progress, the function of B cells is still unclear. Recent studies have shown that B cells play an important role in anti-tumor immunity ( 193 ), and numerous B lymphocyte populations (naive B cells, memory B cells, activated memory B cells) have been found in the TME. B cells are the second adaptive immune cell population found in TME ( 194 , 195 ).…”
Section: Roles Of Exosomes In the Tmementioning
confidence: 99%
“…However, while the role of T cells has made some progress, the function of B cells is still unclear. Recent studies have shown that B cells play an important role in anti-tumor immunity ( 193 ), and numerous B lymphocyte populations (naive B cells, memory B cells, activated memory B cells) have been found in the TME. B cells are the second adaptive immune cell population found in TME ( 194 , 195 ).…”
Section: Roles Of Exosomes In the Tmementioning
confidence: 99%
“…Although many molecular-targeted agents have been developed to treat GC, no agent, except trastuzumab, has shown efficacy as a first-line therapy [ 53 ]. However, advances in genomic analysis have revealed genetic subgroups that are attractive therapeutic targets [ 13 ]. Here, we provide an overview of the development of zolbetuximab for claudin 18.2 (CLDNl8.2) and bemarituzumab for fibroblast growth factor receptor 2b (FGFR2b), which are currently garnering remarkable attention as therapeutic targets.…”
Section: Prospects For Novel Therapies For Advanced Gastric Cancermentioning
confidence: 99%
“…In contrast, GC is often diagnosed at an advanced stage in most Western patients. Notably, the biological nature of GC and differences in therapeutic quality between Eastern and Western countries may affect treatment outcomes [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major risk factors for gastric cancer include bacterial infection, smoking, diet, and alcohol consumption [2]. In recent years, next-generation sequencing technologies have elucidated the landscape of genetic variations in the carcinogenesis of gastric carcinoma [3].…”
Section: Introductionmentioning
confidence: 99%